Effectiveness of Low Molecular Weight Fucoidan and High Stability Fucoxanthin (LMF- HSFX) in Phaeophyta as Bioactivity in Emergency Therapy of Non-Alcoholic Fatty Liver Disease (NAFLD) - Agatri, Norina; Sekar Laranti, Nimas Adiani; Shabrina, Hanifa Nur; Hurulhanifa, Fatmanur (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2024)
Indonesia is a maritime nation with a rich marine ecosystem and biodiversity. The waters are abundant in Phaeophyta (brown algae), which are a significant source of bioactive compounds such as fucoidan and fucoxanthin. These compounds have shown potential in treating Non-Alcoholic Fatty Liver Disease (NAFLD), a metabolic disorder characterized by excessive fat accumulation in the liver, leading to complications such as fibrosis, cirrhosis, and hepatocellular carcinoma. The objective of this study is to evaluate the effectiveness of Low Molecular Weight Fucoidan (LMF) and High Stability Fucoxanthin (HSFx) in the curative treatment of NAFLD. Specifically, the study aims to assess the bioactivity and biocompatibility of LMF-HSFx and compare its efficacy with a placebo group in the treatment of NAFLD. The study used a non-invasive Fibroscan to test Controlled Attenuation Parameter (CAP) and Transient Elastography on NAFLD patients. It included 42 NAFLD patients, divided into two groups: the LMF-HSFx group and the placebo group. The LMF-HSFx group received oral supplementation of 825 mg LMF fucoidan and 825 mg HSFx twice daily for six months. The effectiveness of the treatment was measured through changes in hepatic lipotoxicity, serum markers, and pro-inflammatory cytokines. The results showed significant reductions in hepatic lipotoxicity, serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), total cholesterol, and triglycerides in the LMF-HSFx group. The study also observed significant reductions in pro-inflammatory cytokines (IL-6 and IFN-Î³) and improvements in adiponectin and leptin levels. These findings suggest that the LMF-HSFx combination effectively reduces hepatic inflammation and improves metabolic parameters in NAFLD patients.